BUDAYA ORGANISASI SEBAGAI VARIABEL PEMEDIASI: PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP PEMBERDAYAAN KARYAWAN (Studi Pada PT Petrokimia Gresik) - MARUFAH, JAZILATUL (Jurnal Ilmu Manajemen (JIM), 2019)
PT. Petrokimia Gresik is a manufacturer engaged in fertilizer production and fertilizer marketing as well as the chemical industry. In its activities, PT. Petrokimia Gresik conducts internal communication that aims to improve the quality of human resources in the organization. The purpose of this study was to examine and analyze the influence of transformational leadership on employee empowerment through organizational culture. The sample used in this study was 56 employees in the Human Resources Development Departement of PT. Petrokimia Gresik. The data analysis technique used is Structural Equation Model (SEM) with the smartPLS program. The result of this study indicate that transformational leadership has a possitive effect on employee empowerment, transformational leadership has a positive effect on organizational culture and organizational culture culture capable of mediating transformational leadership toward employee empowerment. Keywords: employee empowerment; organizational culture; transformational leadership.